The People in Arms in the Peoples Entertainment: Cinema and Political Propaganda in Portugal (1916-1917) - Janeiro,Helena Pinto (2013)
This article seeks to contribute to the historiographical debate on First World War propaganda in Portugal. The fact that it was precisely during this war that the first official body concerned with film production appeared (the Photographic and Cinematographic Section of the Army, SFCE) is a strong indication that the First Republic kept pace with the most innovatory aspects of this conflict in the various belligerent countries. In fact, it was precisely at this time that official bodies devoted to cinema appeared in countries such as Great Britain, France and Germany. We start by studying the pioneering experiment in film which made the people in arms the protagonists in the peoples entertainment, in the context of a military and propaganda exercise conducted by the Minister of War, Norton de Matos, in the summer of 1916. The success of this first film was so great that the captain who produced it was asked to set up the SFCE, in time to film the embarkation of the first troops for France, in January 1917. As well as clarifying the origins, objectives and more institutional aspects of the SFCE, which previously had remained obscure, the article presents data about the exhibition and the public reception of films produced by this unit.